EVALUASI EFEK ANTI-DIABETES MELITUS EKSTRAK TERPURIFIKASI Andrographis paniculata (Burm. f.) Nees DAN ANDROGRAFOLID DENGAN PARAMETER INDEKS HOMA-IR - Ignatius Ryan Adriawan; Mohamad Andrie; Rina Susilowati; Suwidjiyo Pramono; Agung Endro Nugroho (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
Diabetes mellitus type 2 was induced by high fat diet and fructose. The insulin resistance and hyperinsulinemia compensatory can be measured by index homeostatic model assessment – insulin resistance (HOMA-IR). Andrographis paniculata (Burm. f.) Nees is a traditional plant can be used to treat diabetes mellitus and the main active compound of this plant is Andrographolide. The objective of this study is to evaluate the effect of purified extract of Andrographis paniculata (Burm. f.) Nees and andrographolide on HOMA-IR index of High fat diet and fructose induced Wistar Rats. This study is quasi-experimental and data analysis was using Kruskal-Wallis test. The result showed that purified extract of Andrographis paniculata and andrographolide decreased HOMA-IR index. Purified extract of Andrographis paniculata 1303,8 mg/kg decreased HOMA-IR index by 82,05 %.